2020
DOI: 10.2147/ccid.s233185
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Skin Lightening Cream Agents – Hydroquinone and Kojic Acid, on the Skin of Adult Female Experimental Rats</p>

Abstract: Introduction: Skin bleaching is the act of using steroid-and chemical-containing products to lighten the skin. Hydroquinone and kojic acid are often used in skin bleaching creams. Hydroquinone was suspected to be harmful. This study investigated the effects of kojic acid and hydroquinone on the skin of adult female Wistar rats and the potential use of aloe vera for amelioration. Materials and Methods: Eighty [n=80] adult female Wistar rats with an average weight of 120 g were randomly divided into eight groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…Hydrophilic agents such as hydroquinone, arbutin, or vitamin C would first contact with sebum, follicular debris, bacteria, and other exogenous materials coating the skin, then penetrate to the skin via their actual pathway through the hair follicle. A previous study suggested that topical hydroquinone could induce follicular inflammation by demonstrating the prominent expression of p56, a marker of cell proliferation, degeneration, and inflammation, in the hair follicles [13]. Furthermore, a high level of facial sebum contents filled in the follicular space can interfere with the follicular drug delivery, especially hydrophilic substances [14].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Hydrophilic agents such as hydroquinone, arbutin, or vitamin C would first contact with sebum, follicular debris, bacteria, and other exogenous materials coating the skin, then penetrate to the skin via their actual pathway through the hair follicle. A previous study suggested that topical hydroquinone could induce follicular inflammation by demonstrating the prominent expression of p56, a marker of cell proliferation, degeneration, and inflammation, in the hair follicles [13]. Furthermore, a high level of facial sebum contents filled in the follicular space can interfere with the follicular drug delivery, especially hydrophilic substances [14].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, vitamin E alone has shown minimal efficacy in the treatment of hyperpigmentation disorders such as melasma [16]. Vitamin C, kojic acid, topical corticosteroids, tretinoin, niacinamide, and salicylic acid are also among the most commonly used topical skin-lightening agents [14,[17][18][19]. The actual efficacy of preparations containing only low percentages of these ingredients has not been fully elucidated [20].…”
Section: Discussionmentioning
confidence: 99%
“…11 In a study done on adult female mice, Aloe vera was found to reduce the harmful topical side effects of hydroquinone. 13…”
Section: Treatment Methods Employed By Patientsmentioning
confidence: 99%